(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
This article deals with two bestsellers by Jane Austen, a famous English novelist of books of romantic fiction. It includes the detailed information about the differences and similarities between “Sense and Sensibility” and “Pride and Prejudice”, written in 1811 and 1813, respectively. Additionally, I mentioned the plots, settings, main characters and literary devices of two novels. This article helps you to know closely about the works by analysing in order to enrich literature basis.